Experimental investigation of the adsorbents using pressure and thermal swing for adsorption and desorption - Z. Mdletshe; V. Msomi; O. Nemraoui (Results in Engineering, 2022)
In this study an experimental investigation was conducted on a single stage falling film evaporator together with a single adsorbent bed. The evaporator produced the water vapour which was flooded into the adsorbent bed using the mechanism of the vacuum pressure swing. After the adsorbent had captured the adsorbate, which was water vapour in this study, it was then released using thermal swing to trigger the desorption of the previously captured adsorbate. The tests were performed at controlled varying pressures conditions below atmospheric pressure. The accumulative mass of the adsorbate on the adsorbent was monitored with an aid of a specially built and installed scale within the adsorbent bed. The adsorbent materials - silica gel and zeolite-that were used in this study were locally supplied by a South African vendor. It was observed that silica gel had the highest adsorption capability of 65 g of water vapour per 200 g of silica gel at controlled experimental testing conditions.